Food niche overlap of three sympatric raptors breeding in agricultural landscape in Western Pomerania region of Poland - Skierczyński, Michał (My University, 2006)
Diet of Common Buzzard (Buteo buteo), Eurasian Kestrel (Falco tinnunculus) and Long-eared Owl (Asio otus) were investigated using a pellet analysis method in the Gryfice Plain in Western Pomerania region of Poland. Data on food composition were obtained from 26 nest localities. Using a pellet analysis, 470 individuals of insectivores, rodents, birds and insects were identified. Microtinae, especially The Common Vole (Microtus arvalis), were the most important prey of all studied raptor species in this region of Poland. Common Buzzard had the broadest food niche comparing to other studied predators. The niche overlap index was greater when compared Buzzard vs. Kestrel (0.87) and Kestrel vs. Long-eared Owl (0.85), than Buzzard vs. Long-eared Owl (0.74)
Keywords: food niche overlap; agricultural landscape; Common Buzzard; Eurasian Kestrel; Long-eared Owl